Therapeutic and Diagnostic Analysis of Cadmium Sulfide Quantum Dots Conjugated with Cysteine, Anticancer Drug and Folate - Mehreen Fatima, Anadil Noel, Zeeshan Abdullah, Kainat Bibi, Shumaila Yousaf, Muhammad Nouman Aziz, Muhammad Farhan Zafar Chaudhry, Madiha Shahzad Lodhi, Fatima Khalid, Ayesha Ameen, Sana Farooq, Qudsia Mushtaq (Pakistan Journal of Medical & Health Sciences, 2022)
Background: Nanotechnology is evolving in the field of cancer drug design and cancer therapy. The ultrafine nanoparticles that have a size range of 1-10nm are called Quantum Dots. The ability to fluorescence has deemed quantum dots as suitable candidate for diagnostic imaging. Upon proper structural arrangement these quantum dots can be engineered to detect specifically cancer cells and deliver anticancer agents to the targeted site for cancer cell apoptosis. Aim: Cadmium sulfide (CdS) nanoparticles conjugated with cysteine were prepared by wet method under high temperature and pressure Methods: Folic acid receptor has shown overexpression in multiple types of cancers therefore the binding of folate to the composite ensures that only the cancer cells are targeted and normal cells remain unaffected. HeLa cells were opted to check the composite activity. Results: Composite showed 23% cell death in the first 2 hours of delivery. FTIR analysis confirmed conjugation of CdS with cysteine and further conjugation of dacarbazine and folate to cysteine. The molecules of folic acid attached to cysteine could be measured to be 2.545× 1018 molecules which were attached to 0.996× molecules of cysteine that were attached 1.66 x molecules of CdS. Similarly, 2.3103 × 1019 of doxorubicin were attached to 0.996× molecules of of cysteine attached to 1.66 x molecules of CdS. Furthermore, the cytotoxic nature of Cadmium Sulfide also gives an advantage two way cancer cell death. Conclusion: Quantum dots attached to specific ligands that bind to cancer antigens, antibodies, proteins, Receptors etc. can be used for effective diagnosis of cancer. They can act as probe and detect thousands of molecules simultaneously by using only a small quantity of nanoComposite. Keywords: Cadmium sulfide, Cancer, Quantum dots, Dacarbazine